Reggio Emilia 2007-2008 the golden jubilee tournament - Marin, Mihail; Garrett, Yuri
This book celebrates fifty years of the famous Italian tournament. All the games are analysed, many of them by the players themselves: those sharing their wisdom include award-winning author Mihail Marin, rising star Ni Hua, Tournament winner Zoltan Almasi and the legendary Victor Korchnoi. In addition, photographs and entertaining stories take the reader behind the scenes at a top-class tournament